(3MGTjI Ydi TQM GdJUQjas - (3fGUQ GdOjf GddbGfis; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s ((3CHh HcQ GdHgGLi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUGdI hGdSdGe Ydi QShd Gddg agPg MhGTi Ydi ehGVY ef TQM JUQja GdZRi ddYdGeI GdJaJGRGfi aJchf gPg GdCdaGX ESJYGQGJ JMbjbjI s
(3BNQgG (B:s
(3bhdg Ydi ebaGd bjd GdCUd ai GSe GdBdI Cf jchf Ydi eaYGd hGdMeO ddg hMOg JeJ HGdNjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
Keywords: (3GdHdGZIs